Akuntabilitas Pemimpin Pendidikan Berbasis Agama, Filsafat, Psikologi dan Sosiologi - Nugraha, Derry; Agusti, Agusti (STKIP PGRI SITUBONDO, 2024)
This study aims to describe and analyze the accountability of educational leaders based on religion, philosophy, psychology and sociology. 1). Based on the religion of Allah SWT as a result of an education that is fair, kind, satisfying, not deceptive, not against rules and not self-contradictory. 2). What is philosophically grounded is a moral responsibility to the rules of logical reasoning that arise from educational acts that must be carried out with substantive, sustained, practical, progressive and reconstructive diligence. . 3). Psychology is based on the emotional responsibility of feeling human about something, the correct character, behavior, and educational actions that should be taken in situations. Four). Sociology is grounded in social responsibility to social status through education and must be practiced in ways that meet the functional needs of society and the stratification of political, economic and social status.